2007
DOI: 10.1109/jlt.2007.903547
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Nonlinear Optical Phenomena in Nanophotonics

Abstract: Abstract-In this paper, we review various numerical methods currently used to model nonlinear optical processes in nanophotonics. Among the different theoretical frameworks that have been used to study nonlinear photonic structures, we particularly focus on the application of both perturbation theory and coupled-mode theory to the analysis of complex nonlinear nanophotonic devices. This description is illustrated on several examples of how these techniques can be used to design photonic-crystal-based nonlinear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 52 publications
2
45
0
5
Order By: Relevance
“…It is shown in (Bravo-Abad et al, 2007) that a  change in the dielectric constant can result in a  variation in the original eigenvalue 0  as: 2 3 00 0 00 2 3 00 0 00…”
Section: Modeling Optical Nonlinearity In Pcsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is shown in (Bravo-Abad et al, 2007) that a  change in the dielectric constant can result in a  variation in the original eigenvalue 0  as: 2 3 00 0 00 2 3 00 0 00…”
Section: Modeling Optical Nonlinearity In Pcsmentioning
confidence: 99%
“…But since for a waveguide / g vk    then it can be shown that (Bravo-Abad et al, 2007) the following approximation is valid:…”
Section: Modeling Optical Nonlinearity In Pcsmentioning
confidence: 99%
See 1 more Smart Citation
“…Material nonlinearities are typically introduced in CMT using perturbation theory, and this has been shown to provide good agreement with full numerical calculations. 8,10,16,17 We note, however, that due to the finite Q-value of any real cavity the perturbation theory should be performed in the framework of non-Hermitian eigenvalue analysis 12,18 as we do here. Although this seems to be largely ignored in the literature, we emphasize that the absolute value of the field in Fig.…”
mentioning
confidence: 93%
“…Recent developments in nanofabrication are enabling fabrication of nanophotonic structures, e.g., waveguides and cavities that confine light over long times and small volumes [17][18][19][20][21], minimizing the power requirements of nonlinear devices [22,23] and paving the way for novel on-chip applications based on all-optical nonlinear effects [18,[24][25][26][27][28][29][30][31][32][33]. In addition to greatly enhancing light-matter interactions, the use of cavities can also lead to qualitatively rich dynamical phenomena, including multistability and limit cycles [34][35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%